2016
DOI: 10.1063/1.4963881
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitivity of InZnO thin-film transistors using a solution process

Abstract: Oxide semiconductor devices play a role in both switches and photo-sensors in interactive displays. During the fabrication of oxide semiconductor devices, the sol-gel solution process that is used to form an oxide semiconductor has various merits, including its simplicity and low cost as well as its good composition controllability. Here, we present the photosensitivity characteristics of an oxide photo thin-film transistor (TFT) created using the InZnO (IZO) sol-gel process. Upon exposure to light, photocurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…We consider InGaZnO to be an extremely well-suited material for this application, taking into account both device cost and possibilities surrounding integration into different systems. If cost-reducing considerations are incorporated into the design of these monitoring devices, for example the use of disposable sensing components, InGaZnO would be a highly suitable candidate as several groups have reported successful solution-processing and printing of thin-films of this semiconductor, alongside other oxide-based materials. On the other hand, if a manufacturer selects an integrated system akin to those found in conventional electronics, InGaZnO thin-films may also be deposited by vacuum-based display manufacturing-type processes, allowing the integration of InGaZnO-based ISFETs with signal processing circuits. The processing flexibility of the InGaZnO material system makes it an excellent candidate to be studied for a variety of monitoring devices, including the flexible and wearable sensors outlined in this study.…”
Section: Resultsmentioning
confidence: 99%
“…We consider InGaZnO to be an extremely well-suited material for this application, taking into account both device cost and possibilities surrounding integration into different systems. If cost-reducing considerations are incorporated into the design of these monitoring devices, for example the use of disposable sensing components, InGaZnO would be a highly suitable candidate as several groups have reported successful solution-processing and printing of thin-films of this semiconductor, alongside other oxide-based materials. On the other hand, if a manufacturer selects an integrated system akin to those found in conventional electronics, InGaZnO thin-films may also be deposited by vacuum-based display manufacturing-type processes, allowing the integration of InGaZnO-based ISFETs with signal processing circuits. The processing flexibility of the InGaZnO material system makes it an excellent candidate to be studied for a variety of monitoring devices, including the flexible and wearable sensors outlined in this study.…”
Section: Resultsmentioning
confidence: 99%
“…A fast photoresponse time is another important feature for a high-performance photosensor. , However, oxygen vacancies (V O ) could be easily induced in oxide semiconductors because of the outdiffusion of oxygen from the oxide semiconductor . These V O can be excited by a light with a lower energy than the band gap of the oxide semiconductor and induce conduction electron carriers into the conduction band. Moreover, optoelectronic characteristics of zinc–oxide (ZnO) depend significantly on ambient gases, such as oxygen . When the oxygen is adsorbed on the ZnO surface, weakly adsorbed O 2 – could be formed and easily desorbed by visible light to create electrons into the conduction band. , Thus, the carrier density can be increased, and the threshold voltage ( V TH ) can be negatively shifted .…”
Section: Introductionmentioning
confidence: 99%
“…To date, among the AOSs with a wide optical band gap, In 2 O 3 and its composites, such as indium zinc oxide (IZO) and indium gallium zinc oxide (IGZO), have been widely used for ultraviolet (UV) photodetectors. , Choi et al reported the photoresponse characteristics of oxide photo-TFTs with IZO fabricated by a sol–gel process . Recently, Chang et al investigated the electrical performance of deep ultraviolet-sensitive a-IGZO TFTs with a double-stack Ga 2 O 3 /SiO 2 gate dielectric .…”
Section: Introductionmentioning
confidence: 99%
“…In a traditional planar phototransistor, the optoelectronic characteristics of field-effect phototransistors (FEPTs) were often seriously restricted by two elements: the interface contact and lateral device architecture. The separation of electron–hole pairs from the AOS to the electrode is considered to be dependent on the channel length and the degree of contact between the AOS and gate dielectric. Unfortunately, a large amount of charge carriers will be captured or recombined in a charge transfer process due to long channel lengths, resulting in low R and D *. Hence, there is an urgent requirement to design a novel device architecture that enables shortening of the length of the channel layer to promote the photoelectric performance of AOS phototransistors. Vertical organic field-effect transistors have been reported to provide ultrashort channel length. , However, oxide photodetectors based on vertical field-effect transistors have not been reported.…”
Section: Introductionmentioning
confidence: 99%